Involvement of D-amino acid oxidase in elimination of free D-amino acids in mice. - Nagata, Y (1989)
The physiological role of D-amino acid oxidase was investigated by using mutant ddY/DAO- mice lacking the enzyme. Free D-amino acid concentrations in the mutant mice were significantly higher than those of control ddY/DAO+ mice in kidney, liver, lung, heart, brain, erythrocytes, serum and urine. The results suggest that the enzyme is involved in the catabolism of free D-amino acids in the body, and that free D-amino acids are also excreted into urine.